Simulation of traffic flow through a toll gate - Shimizu, Hikaru; Hara, Akemi; Kita, Eisuke; Tamaki, Tatsuhiro (Computer Assisted Methods in Engineering and Science, 2007)
This paper describes the simulation of the traffic flow through toll gate. A two-lane road is considered as the object domain and then, the local rules are defined to control the vehicle behavior. First, one simulates the traffic flows through the road with two non-ETC gates or the road with two ETC gates. The maximum traffic amount on the roads with two ETC gates is less than that on the road without gates by about 10%, while, in the case of the roads with two non-ETC gates, the maximum traffic amount decreases by 80%. Next, one simulates the traffic flows through the road with one non-ETC gate and one ETC gate. The traffic amount depends not only on the vehicle occupancy but also on the percentage of ETC vehicles among all driving vehicles.